Does Debt Affect Firm Financial Performance? The Role of Debt on Corporate Governance in Indonesia - Fitri Ismiyanti; Putu Anom Mahadwartha (The Indonesian Journal of Accounting Research, 2013)
This research addresses main question of the conditions of debt-constraint expropriation and debt-facilitate expropriation, and the difference between those conditions on type of group ownership (group or no group-affiliate). Agency theory predicts that debt is bonding and monitoring mechanism for managers' perquisites action. Expropriation of minority shareholders by majority shareholders hurts good corporate governance practices. The expropriation also hurts debtholders value. The research argues that the use of debt will minimize the expropriation level and maintain certain control to managers and majority shareholders, on behalf of minority shareholders and debtholders. The problem of majority versus minority and debtholders spreads widely in Indonesia. This research conducts analytical and statistical methods to examine the roles of debt policy as mechanism of good corporate governance practices in Indonesia. This research argues that debt has difference effect on financial performance based on certain debt characteristic. Two characteristics of debt are debt-constraint expropriation (DCE) and debt-facilitate expropriation (DFE). Different types of ownership, which are group and no group-affiliate, are also examined to support the main issues of DCE and DFE. The result will be useful for economic policy makers; firms level policy makers, investors, academician, and researchers in the area of finance, social science, and humanities. The research tests the main question with four hypotheses using ordinary least squares (OLS) regression and Wald test for coefficient test. The result shows support for differences in effect on debt to performance for DCE (positive effect) and DFE (negative effect). On DCE, no group-affiliate firms have higher positive effect of debt on performance than group-affiliate firms do. However, on DFE due to risk reduction mechanism, group-affiliate firms have less negative effect of debt on performance than no group-affiliate firms do.